The laws of service in Bangladesh - Ābu Bakara, Khandakāra Muhāmmada, 1941- (Rangpur, [Bangladesh] : Mahfuza Khondaker, 1998)
Commentaries with latest case references and amendments of the laws.
Includes few chapters in Bengali.
Includes index.
Keywords: Civil service -- Bangladesh